Local Wisdom In Umpasa Tradition: An Ecolinguistic Perspective - Mery Silalahi (PROSIDING SEMINAR NASIONAL PENDIDIKAN, BAHASA, SASTRA, SENI, DAN BUDAYA, 2023)
This study aims to delineate the values of local wisdom within the oral tradition of Umpasa from an ecolinguistic perspective. The ecolinguistic perspective is supported by communication ethnography studies. Data for this research were collected using observation methods, note-taking techniques (linguistics), complemented with ethnographic conversation methods and recording techniques (ethnography). Data analysis employed the extralingual correspondence method and contextual analysis techniques. The results of the analysis indicate that local wisdom within the oral tradition of Umpasa is manifested through tangible forms of local wisdom such as rocks and water, ulos motifs, and traditional houses; as well as through intangible forms of local wisdom such as proverbs, advice, and poetry. Each form of local wisdom manifests noble values that reflect the collective cultural appreciation of the society. This research examines the values of local wisdom embodied in the oral tradition of Umpasa within Batak society through an ecolinguistic approach and communication ethnography studies. The oral tradition of Umpasa is an inseparable part of the rich and diverse Batak culture, containing advice, proverbs, and songs laden with ancestral wisdom and teachings. Unlike physically tangible local wisdom, Umpasa exists as an intangible heritage transmitted orally, bringing deep understanding of the relationship between humans and nature and culture. These dimensions of local wisdom reflect the collective cultural appreciation of Batak society. The implications of this research involve understanding and promoting the preservation of local culture and enhancing appreciation for local wisdom within Batak society and beyond